مزدور بچوّں (چائلد لیبر) کے حقوق اور ہماری ذمہ داریاں سیرتِ طیبہﷺ کی روشنی میں: Child labor rights and our responsibilities in the light of Seerat-e-taibba - Arshad, Dr. Muhammad; Ahmad, Rabia (Al-Amīr Research Journal for Islamic Studies, 2024)
This article relates to “Child Labor and Our Responsibilities” and the tranny and biased behavior with the children. It has been stressed in the article who the Holy Prophetﷺ opposed the disparity with children in the light of the Islamic teaching. In Europe and America including Muslim countries the tendency of child labor has increased to such and alarming state that the future of poor, helpless and homeless children is in jeopardy. In our motherland, out of millions of new born babies, except a few thousands, innumerable kids are facing numerous economic, social, ethical, medical, judicial and family problems, millions of kids begin a life of slavery even at the age of 5 years and they are bound coercion and oppression. They are badly tortured and oppressed by their own relatives and they strangers who take advantage of their childhood and innocence. Now in Pakistan including Karachi millions of kids are dragging the burden more than their age. Among these millions work in the factories at a negligible salary are serve as labor on the roads, roundabouts or workshops etc. It is regrettable that on one takes the responsibility to protect the rights of these uneducated, deprived and oppressed children. Who will take the charge to provide them education? The Government and people both should take the responsibility if we shirk our responsibilities we will face disgruntled generation in near future who will inclined to take revenge of cruelty, oppression and deprivation. In short we can say that child labor is one of the worst problems of the modern world. Especially, every country of the third world is involved in this problem. It is impossible to save the downtrodden people from the cruelty of industrious and influential people without proper legislation. We can earn blessings in their world and thereafter through gaining light from the lives of the Prophet Muhammad ﷺ and his companions. Key Words: Sirah of Holy Prophetﷺ, Child Labor, Homeless, kids, Pakistan.